Remarks on the Stone Circle of Callernish (Proceedings of the Society of Antiquaries of Scotland, 1862)
Notice of a talk given by Lieutenant J W L Thomas on the stone circle at Calanais, including photographic and stereographic views he created during his surveying expedition.